2013
DOI: 10.1111/cdev.12165
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Building Blocks: Preschoolers' Spatial Assembly Performance Relates to Early Mathematical Skills

Abstract: This study focuses on three main goals: First, 3-year-olds' spatial assembly skills are probed using interlocking block constructions (N = 102). A detailed scoring scheme provides insight into early spatial processing and offers information beyond a basic accuracy score. Second, the relation of spatial assembly to early mathematics skills was evaluated. Spatial skill independently predicted a significant amount of the variability in concurrent mathematics performance. Finally, the relationship between spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(229 citation statements)
references
References 69 publications
11
194
3
3
Order By: Relevance
“…Spatial visualization tasks requiring mental transformations of 2D and 3D objects were found to correlate not only with measurement skills (Casey et al 2011), but also with students' performance on arithmetic word problems (Hegarty and Kozhevnikov 1999) and counting skills (Kyttälä et al 2003). Although most studies on the relation of spatial abilities and mathematics performance focused on older children and adolescents, it has also been shown that at age three, children's ability to count, represent number, and do simple addition and subtraction problems is related to their spatial skills (e.g., Gunderson et al 2012;Verdine et al 2014). Moreover, in line with the found concurrent and predictive relationship between spatial skills and mathematics achievement, there is evidence that enhancing children's spatial skills can contribute to improving their mathematical skills (Newcombe 2010;Cheng and Mix 2014).…”
Section: Mathematics Abilitymentioning
confidence: 99%
“…Spatial visualization tasks requiring mental transformations of 2D and 3D objects were found to correlate not only with measurement skills (Casey et al 2011), but also with students' performance on arithmetic word problems (Hegarty and Kozhevnikov 1999) and counting skills (Kyttälä et al 2003). Although most studies on the relation of spatial abilities and mathematics performance focused on older children and adolescents, it has also been shown that at age three, children's ability to count, represent number, and do simple addition and subtraction problems is related to their spatial skills (e.g., Gunderson et al 2012;Verdine et al 2014). Moreover, in line with the found concurrent and predictive relationship between spatial skills and mathematics achievement, there is evidence that enhancing children's spatial skills can contribute to improving their mathematical skills (Newcombe 2010;Cheng and Mix 2014).…”
Section: Mathematics Abilitymentioning
confidence: 99%
“…One study found that teenagers who built taller block models had better math skills than teenagers whose block models tumbled at a shorter height [1]. Another study found that 3-year-old children who could correctly build a block model by following instructions had better math skills [2]. One more study found that children who built complicated models when they were in preschool (3-to 4-year olds) had better math scores in grade 7 (as 12-year olds) [3].…”
Section: What Researchers Already Knowmentioning
confidence: 99%
“…17 There is a large experimental literature on these issues, often influenced by Piaget; for a recent overview focussing on block play and the presence or absence of the relevant skills in three year olds see Verdine et al 2013. 18 I am very grateful to Lucy Allais, John Callanan, Colin McLear, Dennis Schulting, Nick Stang and Clinton Tolley for discussion and comments on this material. I am also indebted to the editor and two anonymous referees for their extremely helpful remarks on an earlier draft.…”
Section: The Categories and Relational Synthesis: The Axiomsmentioning
confidence: 99%